Indonesia Cyber Security : Urgency To Establish Cyber Army In The Middle Of Global Terrorist Threat - Setiawan, Rangga (Journal of Islamic World and Politics, 2018)
This research focused on how on the year of 2030 Indonesia will gain better governance in order to countermeasures terrorist threats, fairer human rights in terms of privacy and security in information and technology, also stronger Indonesia’s national cyber security. Cases are taken firstly from nowadays Indonesia social conflict which started from the internet as society’s first source of information regardless the validity of information and secondly from Indonesia’s foreign policies towards private technology deals. By using the concept of cyber power and national security as paradigm, this research described how Indonesia going securely, equally, rapidly forward in line with globalization opportunities and technology dependencies. While minimizing invalid and provocative information as terrorist threat to Indonesia’s sovereignty and integrity by improving the security of intellectual and on-field assets by integrating academia, military aspects and people’s contribution to accelerate Indonesia’s national potential in cyber security.